Perancangan Dashboard sebagai Alat Bantu Memonitor Departemen Produksi pada PT X - Steven Davian; Siana Halim (Jurnal Titra, 2022)
PT. X is a furniture company founded in 2006. The PT. X processes logs into ready-use items such as cabinets, tables, chairs, and other furniture. Currently, In monitoring the production department, the company only rely on reports of production process results/outputs for each work station that are recorded manually every day on paper by admin workers in the field. Moreover, there is no modern visual information tool that can help companies evaluate the performance of the production department in detail. This causes the company difficulty in evaluating the performance of the production department that has been done so far. Therefore, this study aims to design a database and a dashboard to evaluate the performance of the production department. Dashboards are made using software that can be connected via the internet so that the processing and visualization of the data presented is real-time data. In addition, the designed database and dashboard help the company monitor and evaluate the production process in the production department.